HUBUNGAN POSISI TUBUH DENGAN TIMBULNYA NYERI PUNGGUNG BAWAH PADA PEKERJA BANGUNAN DI PT. CIPTA NUGRAHA SANTOSA - Suhardjanto . (STIKES DUTAGAMA KLATEN, 2017)
Background : Safety and health at work apply construction / building. As for the consequences arising from the work of building one of which is lower back pain. The results of interviews with 10 workers at the PT building. Cipta Nugraha Santosa 5 of 10 construction workers have experienced low back pain and they do not pay attention to the importance of correct posture while working. Objectives : To determine the relationship of the body position with the onset of low back pain. The method of research : Using the analytic correlation with cross-sectional survey approach. Population and sample in this study 68 construction workers who worked at PT. Cipta Nugraha Santosa. Sampling with total sampling. Analysis using Pearson Product Moment Correlation test. Result : Pearson product moment correlation test showed P-value = 0.000 which is smaller than the value sigifikan 5% level (0.05), and the results count r = 0.658 is greater than the table r = 0.235. Conclusion : There is a significant relationship between body position with the onset of low back pain in construction workers at PT. Cipta Nugraha Santosa.